Análisis jurídico y criminológico de las políticas penitenciarias entre las Repúblicas de Ecuador y El Salvador - Delgado Cabrera, Anyely Tatiana (2023)
The present Curricular Integration Project titled: “Legal and Criminological Analysis of Penitentiary Policies between the Republics of Ecuador and El Salvador” is motivated by the fact that a penitentiary system is fundamental in each society, as it allows for the strengthening and contribution to public security in a territory through the social rehabilitation of those individuals who disrupt it. While this is the positive aspect known about the subject, the reality perceived is different. In the majority of Latin American countries, correctional facilities not only fail to provide areas for treatment but, in some cases, contribute to the development and improvement of criminal techniques among offenders. In other cases, they deprive these individuals of their freedom for long periods of time without any prior objective that truly focuses on their social rehabilitation. This is how the penitentiary centers in Ecuador and El Salvador are managed. Despite Ecuador currently facing a serious prison crisis due to intense conflicts within different correctional facilities caused by power disputes and control over drug trafficking, resulting in hundreds of violent deaths that highlight the government's ineffectiveness in dealing with these incidents, and the lack of a strategy to put an end to these acts, the only alternative that has been resorted to is confrontations between police and military forces against criminals. This poses a serious risk to the lives of many individuals, including innocent people. On the other hand, although El Salvador has made history with authorities managing to restore calm to its citizens by imprisoning those individuals who stain and corrupt the rest of society, there is a side of the story that remains untold or that the State tries to suppress. Several sources mention that many arrests have been arbitrary and illegal, and many of the detainees have nothing to do with the commission of criminal acts, nor are they part of criminal structures according to their testimonies. This results in a serious violation of their human rights, as they are denied their defense and sentenced criminally. The severe overcrowding, the strange deaths that have occurred within penitentiary centers, and violations of citizens' rights, and consequently the country's own laws, cast doubt on whether the penitentiary policies in El Salvador are truly advantageous as claimed. Within this graduation project, the corresponding methodology was applied to achieve the established objectives. The technique of conducting surveys and interviews with professionals in the field was used to obtain diverse opinions based on the study of penitentiary policies. Additionally, various materials and methods were utilized to contribute to a more comprehensive research.